Tata Kelola Perbatasan yang Berkelanjutan: Sinergi Lintas Sektor untuk Pembangunan dan Keamanan di Merauke - Tuakara, Yulianus (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the sustainable border governance model by emphasizing cross-sector synergy, as well as identifying supporting factors, obstacles, and formulating recommendations for improving governance in the Merauke border area. Using a qualitative approach with a case study design, the study was conducted in Sota District, Merauke Regency, which is a national strategic area directly bordering Papua New Guinea. Data were collected through in-depth interviews, Focus Group Discussions (FGDs), field observations, and document studies involving various stakeholders, such as central and regional governments, security forces, traditional leaders, business actors, and NGOs. The results of the study indicate that cross-sector synergy in border governance is still sectoral and has not been institutionalized systematically. The main obstacles include regulatory fragmentation, overlapping authority, and low local capacity. However, there is potential for synergy through collaborative practices involving indigenous peoples and formal institutions. This study recommends strengthening cross-sector coordination forums, policy harmonization, and developing a co-production-based governance model. These findings provide a conceptual contribution to the border governance literature and offer an operational model for the formulation of sustainable development policies in Indonesia's strategic border areas